Defective glutamate and K+ clearance by cortical astrocytes in familial hemiplegic migraine type 2. Issue 8 (27th June 2016) - Capuani, Clizia; Melone, Marcello; Tottene, Angelita; Bragina, Luca; Crivellaro, Giovanna; Santello, Mirko; Casari, Giorgio; Conti, Fiorenzo; Pietrobon, Daniela
Abstract: Migraine is a common disabling brain disorder. A subtype of migraine with aura (familial hemiplegic migraine type 2: FHM2) is caused by loss‐of‐function mutations in α2 Na +, K + ATPase (α2 NKA), an isoform almost exclusively expressed in astrocytes in adult brain. Cortical spreading depression (CSD), the phenomenon that underlies migraine aura and activates migraine headache mechanisms, is facilitated in heterozygous FHM2‐knockin mice with reduced expression of α2 NKA. The mechanisms underlying an increased susceptibility to CSD in FHM2 are unknown. Here, we show reduced rates of glutamate and K + clearance by cortical astrocytes during neuronal activity and reduced density of GLT‐1a glutamate transporters in cortical perisynaptic astrocytic processes in heterozygous FHM2‐knockin mice, demonstrating key physiological roles of α2 NKA and supporting tight coupling with GLT‐1a. Using ceftriaxone treatment of FHM2 mutants and partial inhibition of glutamate transporters in wild‐type mice, we obtain evidence that defective glutamate clearance can account for most of the facilitation of CSD initiation in FHM2‐knockin mice, pointing to excessive glutamatergic transmission as a key mechanism underlying the vulnerability to CSD ignition in migraine. Synopsis: FHM2 is a rare monogenic form of migraine with aura caused by loss‐of‐function mutations in the astrocytic α2 Na, K ATPase. Investigating the mechanisms underlying the facilitation of cortical spreading depression (CSD) in a genetic mouse model of FHM2 uncovers insights into migraine pathophysiology. The rates of clearance of glutamate and K + released during cortical activity are both reduced in heterozygous FHM2‐knockin mice with 50% reduced expression of the α2 Na, K ATPase (NKA). In FHM2‐knockin mice, the membrane density of the glutamate transporter GLT‐1 is about 50% reduced in astrocytic processes surrounding cortical excitatory synapses, but is unaltered in axon terminals. The relative impairment of glutamate clearance in FHM2‐knockin mice is activity dependent. Most of the facilitation of CSD initiation and a large fraction of the facilitation of CSD propagation in FHM2‐knockin mice are due to the defective glutamate clearance by cortical astrocytes. Abstract : FHM2 is a rare monogenic form of migraine with aura caused by loss‐of‐function mutations in the astrocytic α2 Na, K ATPase. Investigating the mechanisms underlying the facilitation of cortical spreading depression (CSD) in a genetic mouse model of FHM2 uncovers insights into migraine pathophysiology.